Implementing Warehouse Management System in Stationery Store - Suwarno Suwarno; Ryo Kusnadi (ConCEPt - Conference on Community Engagement Project, 2021)
Happy Stationery is a Stationery Store which located in Komplek Tanjung Pantun, Batam. The Company has inventory issue, because they record the product information with paper-based and unstructured excel. Warehouse Management System is a management job that is to organize warehousing problems. In this research, data collection was done by authors by in the form of interviews and observations. And we use SDLC as Development Methodologies. The result of this research was Web Based system which can fullfill the user requirement. this research shows that the implementation of warehouse management system has improved the inventory management process in the store